A Critique on the Book Analysis of Public Policy: Concepts, Approaches, Models, and Processes - Hadi Karami; Davood Kiakojouri (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Analysis of Public policy is a new trend of public administration in prestigious universities that studies the role of analysts in formulating and implementing public policy and providing different styles of analysis. Policy analysis is a way to formulate and identify problems in order to search for possible solutions. For this purpose, the book Analysis of Public Policy: Concepts, Approaches, Models, and Processes, Tehran: University of Tehran Press. 2018. 272 p. ISBN 6-7092-03-964-978 has been selected and criticized. This research is of content analysis type and is applied in terms of critical implementation. In this regard, first, the creator and descriptive form and content of the work are introduced and then evaluated and analyzed in three dimensions of appearance, structure and content. The evaluation shows that this book, while having its own advantages and strengths, needs to be reviewed and corrected in the above three dimensions, especially the production of appropriate content with general policy analysis.